Working Together and Being Physically Active Are Not Enough to Advise Uniformly and Adequately Low Back Pain Patients: A Cross-Sectional Study - C. Praz; J. Ducki; M. L. Connaissa; P. Terrier; P. Vuistiner; B. Léger; F. Luthi (Pain Research and Management)
The profession of the health-care providers (HCPs) influences their recommendations to the patients. Conversely, interdisciplinarity seeks to challenge such differences, so that the patient receives one single and consistent therapeutic message. Some studies also suggest associations between HCPs life habits and recommendations. Our hypotheses were (1) that despite interdisciplinary work, the profession remains a predictor of recommendations and (2) that HCPs who are more physically active recommend more activity. Three clinical vignettes were presented to a group of experts of low back pain (LBP) (guidelines), and 20 physicians, 22 physiotherapists, and 23 nurses to assess how they evaluate the symptoms and pathologies of LBP patients and how much work and physical activity they recommend. Physical activity was assessed with accelerometers and questionnaires. Some interprofessional differences remained present within an interdisciplinary team. The nurses were more restrictive and further away from the guidelines. The physicians were the most in line with them. The physiotherapists recommend as much physical activity, but less work activity than the physicians. The level of physical activity of the HCPs is not associated with their recommendations. To ensure a clear and unique message, educational actions may be undertaken to promote the biopsychosocial model and clarify the guidelines.